Clotrimazole and econazole inhibit Streptococcus mutans biofilm and virulence in vitro. (January 2017) - Qiu, Wei; Ren, Biao; Dai, Huanqin; Zhang, Lixin; Zhang, Qiong; Zhou, Xuedong; Li, Yuqing
Highlights: Clotrimazole and econazole showed bactericidal activity on S. mutans . Clotrimazole and econazole inhibited S. mutans biofilm formation and virulence. Clotrimazole and econazole exhibited both antifungal and antibacterial activities. Abstract: Objective: : The aim of this study was to determine the inhibitory effect of eight antifungal drugs on S. mutans growth, biofilm formation and virulence factors. Methods: The actions of antifungal drugs on S. mutans were determined by recovery plates and survival kinetic curves. Biofilms were observed by scanning electron microscopy and the viable cells were recovered on BHI plates, meanwhile biofilms were stained by BacLight live/dead kit to investigate the biofilm viability. Bacteria/extracellular polysaccharides staining assays were performed to determine the EPS production of S. mutans biofilms. Acidogenicity and acidurity of S. mutans were determined using pH drop and acid tolerance assays, and the expression of ldh gene was evaluated using qPCR. Results: We found that clotrimazole (CTR) and econazole (ECO) showed antibacterial activities on S. mutans UA159 and S. mutans clinical isolates at 12.5 and 25 mg/L, respectively. CTR and ECO could also inhibit S. mutans biofilm formation and reduce the viability of preformed biofilm. CTR and ECO affected the live/dead ratio and the EPS/bacteria ratio of S. mutans biofilms. CTR and ECO also inhibited the pH drop, lactate acid production, and acid tolerance. The abilities of CTR and ECO to inhibit S. mutans ldh expression were also confirmed. Conclusions: We found that two antifungal azoles, CTR and ECO, had the abilities to inhibit the growth and biofilm formation of S. mutans and more importantly, they could also inhibit the virulence factors of S. mutans.